Analisis Pengendalian Persediaan Bahan Baku pada Produksi Fire Door Menggunakan Metode Economic Order Quantity (EOQ). - Nadira Aisyah Setyawan; Renanda Nia Rachmadita; Dian Asa Utari (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
According to the minister of industry, despite being under pressure due to the Covid-19 pandemic, a number of industrial sub-sectors grew very high in 2021. With this increase, the company finally carried out an evaluation. PT.AAM is still not optimal in meeting the supply of raw materials for fire door production. The main cause that often occurs is the large number of purchases of raw, causing hoarding which can affect the total cost of raw material inventory. Researchers will analyze these problems using the Economic Order Quantity method. The results using EOQ can result in inventory costs being decreased by an average of Rp.1.296.922. with less ordering frequency and optimum cycle. The reorder has been determined by the number of calculations from the reorder point.